A portrait of electricity and magnetism course from the perspective of Outcome-Based Learning (OBE) curriculum in higher education - Diniya, Diniya; Rochintaniawati, Diana; Syarif, Muhammad Ilham; Oshima, Ryugo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to observe and reveal the process of planning and implementation of the Electricity and Magnetism course program from the perspective of the Outcome-Based Education (OBE) curriculum in higher education. The participants involved in this study were one lecturer and 29 students of the Natural Science Education study program at one of the state universities in Pekanbaru City, Riau. Data collection was conducted in the period of April - May 2024. Data collection techniques were carried out through observations of learning implementation and interviews with lecturers in the Electricity and Magnetism course program as well as document analysis of the Semester Learning Plan (SLP) and practice questions. The results of data analysis show that administratively the course planning in the form of SLP has met the rules of the OBE approach. However, in reality, the strategies of lectures, discussions, and practice questions used in class are not enough to support the expected CLO. In the Science Education undergraduate curriculum, Electricity and Magnetism courses are included in the intermediate-level study program course group. In conclusion, although the Semester Learning Plan (SLP) document shows compliance with the OBE approach, the teaching strategies including lectures, discussions, and practice problems-have not fully supported the achievement of the expected CLO.